New insights into RAS in head and neck cancer - Jagadeeshan, Sankar; Novoplansky, Ofra Z.; Cohen, Oded; Kurth, Ina; Heß, Jochen; Rosenberg, Ari J.; Grandis, Jennifer R.; Elkabets, Moshe (Biochimica et biophysica acta. Reviews on cancer, 2023)
RAS genes are known to be dysregulated in cancer for several decades, and substantial effort has been dedicated to develop agents that reduce RAS expression or block RAS activation. The recent introduction of RAS inhibitors for cancer patients highlights the importance of comprehending RAS alterations in head and neck cancer (HNC). In this regard, we examine the published findings on RAS alterations and pathway activations in HNC, and summarize their role in HNC initiation, progression, and metastasis. Specifically, we focus on the intrinsic role of mutated-RAS on tumor cell signaling and its extrinsic role in determining tumor-microenvironment (TME) heterogeneity, including promoting angiogenesis and enhancing immune escape. Lastly, we summarize the intrinsic and extrinsic role of RAS alterations on therapy resistance to outline the potential of targeting RAS using a single agent or in combination with other therapeutic agents for HNC patients with RAS-activated tumors.
Online verfügbar: 22. August 2023, Artikelversion: 31. August 2023
Gesehen am 07.12.2023